Program Inovasi “Berkibar” Berantas Kurang Gizi pada Ibu Hamil dan Balita Risiko Tinggi - Yustanta, Brivian Florentis; Mulyati, Sesaria Betty (STIKES dan AKZI Karya Husada Kediri, 2024)
Chronic Energy Deficiency (CED) in pregnant women and stunting in children under five are two main problems that affect the health of future generations. The aim of this community service activity is to improve the nutritional and health status of pregnant women with CED and stunting toddlers through comprehensive and integrated interventions, in order to create a healthy, intelligent and productive generation. In this activity, there were a target number of 10 CED pregnant women and 7 stunted toddlers. This service was carried out on June 17 - 26 2024 in Bungah Village, Bungah District, Gresik Regency. Based on the results of this service, it was found that the increase in the average weight of pregnant women for 1 weeks was 1 kg, the increase in the average weight of toddlers for 1 week was 0.8 kg, the increase in knowledge of parents and pregnant women after attending education was 80 kg. %, the percentage of mothers who provide exclusive breastfeeding increased by 10%, the number of pregnant women who received providing additional food was 10, the number of babies under five who received providing additional food was 7, the frequency of providing additional food distribution was once every month and evaluation every week, the number of families actively participating in mentoring activities as many as 17 families and the number of health workers who received training on CED pregnant women and stunting was 85%. The